Current trends in addressing environmental and social risks in mining and mineral supply chains by regulatory and voluntary approaches - Gudrun Franken; Philip Schütte (Mineral Economics, 2022)
Mining activities have always raised environmental and social concerns due to their impact on natural resources and people. During the last decade, the stakeholder base expected to respond to these sustainability concerns has broadened from directly involved parties to a range of indirect stakeholders along the downstream mineral value chain. These stakeholders variably engage in reporting, supplier risk assessments, exercising supply chain due diligence, third party assurance, and corporate social responsibility measures. This trend reflects a combination of societal, investor, and regulatory pressure as well as industry self-regulation along the supply chain. The present article examines this development from the complementary perspectives of international regulations and voluntary industry and multi-stakeholder initiatives affecting the industrial and the artisanal mining sector as well as the associated mineral supply chains. To this end, we provide an introductory analysis on the global uptake, implementation challenges, and lessons learnt with regard to both regulatory developments and voluntary initiatives. Key challenges identified include a misalignment between local reforms and international efforts, heterogeneous downstream market requirements, and evasive strategies as well as gaps to report on and achieve positive local sustainability impacts, partly brought about by emphasising corporate risk management over local community priorities. Meaningful stakeholder dialogue and increased local ownership are key factors to overcome some of these challenges.
Keywords: 660; Risk assessment; Mining; Sustainability initiatives; Due diligence; Regulation; Mineral supply chains